Co-effects of C/Ag dual ion implantation on enhancing antibacterial ability and biocompatibility of silicone rubber. (4th September 2020) - Zhou, Xuan; Zhou, Xin; Yan, Rongshuai; Shi, Xiaohua; Du, Yichen; Chen, Yao; Yu, Yao; Fan, Dongli; Zhang, Yiming
Abstract: Although silicone implants are the most popular choice around the world for breast augmentation, reconstruction, and revision, due to the poor antibacterial properties and limited biocompatibility of silicone rubber (SR), one of the major complications, capsule contracture, is a lingering problem. To overcome the two main shortcomings, a dual ion implantation technique was applied to modify the surface of SR with the basic skeleton element of organic matter, carbon (C) and the broad-spectrum bactericide, silver (Ag). We present surface characterization, toxicological effects, and evaluation of the mechanical, antibacterial and biocompatible properties of C and Ag co-implanted SR (C/Ag−SRs). After ion implantation, surface roughness and tensile strength of these new materials increased. Biotoxicity was fully assessed by in vitro experiments on human fibroblasts and in vivo experiments on rats, showing that the low-Ag groups met safety standards. Both the anti-bacterial adhesion and bactericidal abilities of C/Ag−SRs were superior to those of SR, which had few antibacterial activities, especially against Staphylococcus epidermidis . With respect to biocompatibility, the adhesion of fibroblasts was promoted, while their proliferation was moderately inhibited on ion-implanted surfaces. After subcutaneous implantation in rats for 7, 30, 90 and 180 d, the capsular thickness around C/Ag−SRs was significantly lower than that around the SR. Additionally, there was no difference in the inflammatory reaction after 7 d of retention in vivo between C/Ag−SRs and SR. The results demonstrate that C/Ag−SRs are desirable shell materials for breast implants.